1998
DOI: 10.1152/jappl.1998.84.3.980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced bronchial circulation on lung fluid flux after smoke inhalation in sheep

Abstract: We determined the effect of reduced bronchial blood flow on lung fluid flux through changes in lung lymph flow, lung wet weight-to-dry weight (wet/dry) ratios, and pulmonary microvascular reflection coefficient (sigma). In the first of two surgical procedures, Merino ewes (n = 21) were surgically prepared for chronic study. Five to seven days later, in a second operation, the bronchial artery of the injection group (n = 7) was ligated, and 4 ml of 70% ethanol were injected into the bronchial artery to cause sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
3
40
1
Order By: Relevance
“…*Signifi cant difference (P < 0.05) from baseline values delayed in onset. 10,13,20 In contrast to the inability of K2.2 to reduce burned tissue permeability, it signifi cantly attenuated lung permeability changes in the present study. These fi ndings are in accordance with those of a previous report suggesting the benefi cial effect of the anti IL-8 antibody on smoke inhalation.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…*Signifi cant difference (P < 0.05) from baseline values delayed in onset. 10,13,20 In contrast to the inability of K2.2 to reduce burned tissue permeability, it signifi cantly attenuated lung permeability changes in the present study. These fi ndings are in accordance with those of a previous report suggesting the benefi cial effect of the anti IL-8 antibody on smoke inhalation.…”
Section: Discussioncontrasting
confidence: 79%
“…The details of the smoking procedure and the chemical composition of the smoke have been described previously. 13 After smoke insuffl ation, another 20% BSA third-degree burn was infl icted on the fl ank of the other side. A Foley catheter was placed in the bladder to measure urine output.…”
Section: Burn and Smoke Inhalation Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a marked increase (> 20-fold) in airway blood flow after smoke inhalation injury [21]. In the present study, we also noted this airway hyperaemia, which confirmed the findings of a previous report from our laboratory [3].…”
Section: Figure 5 Effect Of Ketorolac On CI (A) and Lvswi (B)supporting
confidence: 93%
“…This has led to clinical use of nebulized heparin in the treatment of burned patients with inhalation injury (Desai et al, 1998). In addition, considering that this airway injury might play an important role in the parenchymal damage, we determined the role of the bronchial circulation in the pulmonary injury (Abdi et al, 1991;Sakurai et al, 1998). We discovered that limiting the bronchial circulation markedly reduced the parenchymal damage seen with smoke inhalation.…”
mentioning
confidence: 99%